About role of adhesive and cohesive interactions in cement systems; Journal of Physics: Conference Series; Vol. 1118 : International Conference Complex equipment of quality control laboratories - Sarkisov Yu. S. Yury Sergeevich; Rakhmanova I. A. Irina Anatoljevna; Gorlenko N. P. Nikolay Petrovich; Afanasjev D. A. Dmitry Anatoljevich; Solonitsina N. O. Nataljya Olegovna; Debelova N. N. Nataljya Nikolaevna; Ikonnikova L. F. Liubov Fedorovna (2018, 2018)
Title screen